Pembuatan Paket Agrowisata Di Desa Wisata Sanda, Tabanan - Moh Agus Sutiarso; I Nyoman Arto Suprapto; Utik Kuntariati (Jurnal Pengabdian kepada Masyarakat Radisi, 2025)
This community service program is located in Sanda Village, Tabanan Regency, Bali. The problems faced by the target partners of the program (the Sanda Village Tourism Awareness Group/Pokdarwis) include the lack of skills among Pokdarwis members in developing rural tourism products based on agrotourism; limited synergy and coordination between Pokdarwis and other community groups in Sanda Village; and insufficient involvement of local stakeholders in supporting tourism development in the village. The solutions implemented include providing assistance in designing agrotourism packages, assisting in the development of interpretation materials for agrotourism activities, as well as facilitating improved coordination and collaboration with other community groups to support tourism product development in Sanda Village. The outputs achieved include: 1) The creation of agrotourism packages such as Farming Trekking, River and Rice Field Exploration, and a Plowing the Rice Field attraction; 2) Improved promotional facilities through content specifically highlighting agrotourism; 3)The formulation of an integrated institutional model for agrotourism development. This community service initiative has been positively and enthusiastically received by the people of Sanda Village, and the sustainability of the program is highly expected.